Perspektif Pendidikan Islam Tentang Peran Guru Sebagai Pengajar dan Pembimbing dalam Membentuk Karakter Peserta Didik - Andi Hapidah (Institusi Agama Islam Negeri (IAIN) Bone, 2025)
Education is an effort to improve the quality of human life through the advancement of knowledge and structured learning experiences. Among its various branches, Islamic education holds a distinctive role. In the Islamic perspective, teachers are not merely knowledge transmitters, but also role models and guides who instills moral, spiritual, and social values. This dual role has a significant impact on shaping students’ character, enabling them to develop values that serve as a strong foundation in facing contemporary challenges. This study aims to analyse the role of teachers as both educators and mentors within the framework of Islamic education, as well as its implications for character building. In today’s context, teachers are expected not only to transfer knowledge but also to nurture students’ moral, spiritual, and social development amid the pressures of globalization and the rapid flow of information. Using a literature study method, this research examines relevant books, journals, and other academic sources. Findings indicate that in Islamic thought, the teacher’s role extends beyond cognitive functions to include affective and psychomotor development, integrated through the concepts of ta’lim, tarbiyah, and ta’dib. Teachers are regarded as murabbi, mu’allim, mudarris, and mursyid, responsible for instilling Islamic values such as trustworthiness, patience, honesty, and compassion. The integration of knowledge transfer with character formation through role modelling, habituation, and daily interactions proves effective in nurturing students with noble character. The study concludes that teachers hold a strategic role in building a generation that is both intellectually competent and morally grounded in Islamic teachings. Supportive educational policies, continuous professional development, and collaboration with parents and communities are crucial to optimizing this role.